Global Warming: Testing for Direct and Indirect Effects of Temperature at the Interface of Primary Producers and Herbivores Is Required - von Elert, Eric; Fink, Patrick (Frontiers in Ecology and Evolution, 2018)
In aquatic food webs, global warming may affect higher trophic levels by increased surface water temperatures and by changing the biochemical composition of phytoplankton. Correlations have suggested that growth of Daphnia, a major consumer of phytoplankton in freshwaters, is limited by a low content of the polyunsaturated fatty acid eicosapentaenoic acid (EPA) in natural phytoplankton and thus by food quality. Here we used the EPA-free green alga Chlamydomonas klinobasis and Daphnia magna to test for such food quality effects. The alga was grown in continuous cultures at 15°C, 20°C and 25°C and, different from other studies, dilution rates accounted for the effects of temperature on algal growth. This resulted in a maximum content of total fatty acids, of total PUFAs, of n-3 PUFAs and of α-linolenic acid when grown at 20°C, whereas at 15°C the lowest content of n-6 PUFAs and a threefold higher n-3/n-6 ratio than at 20°C and 25°C were observed. Unexpectedly the PUFA content did not show a maximum at 15°C. Growth experiments with D. magna were performed at 15°C, 20°C, and 25°C. With C. klinobasis grown at 20°C, Daphnia somatic growth rates increased with temperature. When the alga was raised at the same temperature as Daphnia, somatic growth rates of Daphnia increased with temperature, and supplementation indicated EPA-limitation at 15°C only. At 15°C and at 25°C, Daphnia growth was significantly higher on C. klinobasis raised at the respective temperature than on the same alga grown at 20°C. Hence, estimation of temperature effects on Daphnia growth requires to grow the food at the same temperature. At 15°C Daphnia newly built biomass had the highest content in total PUFAs and in α-linolenic acid, whereas the EPA-content was highest at 20°C. The content of n-6 PUFAs increased with temperature, which lead to the highest ratio of n-3/n-6 PUFAs at 15°C. This reflects increased PUFA-assimilation but decreased EPA-synthesis in Daphnia at lower temperatures. The results indicate that only if both algal food and consumer are grown at the same temperature, food quality effects of global warming can be more precisely predicted.